Performance assessment of physical education teachers in schools - Bella Shasi Saraswara; Ali Maksum; Advendi Kristiyandaru (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
This study aims to reveal the performance of physical education teachers in terms of pedagogic, professional, personality and social competence and their impact on the physical fitness of junior high school students in Pekanbaru City, Riau. This research is a survey type with a questionnaire (Likert scale) as the instrument with a total sample of 33 physical education teachers at 10 junior high schools in Pekanbaru City who were taken by random sampling. Assessment of teacher pedagogical competence was given by the school principal, professional competence by the vice principal for curriculum, and personality and social competence by the vice principal for public relations analyzed quantitatively. The results showed that the performance of junior high school physical education teachers in Pekanbaru City, measured by referring to the four competencies, is very good. Personal competence indicates the highest score with a percentage of 93.5%, followed by social competence at 91.01%, professional competence at 89.56%, and pedagogical competence at 89.3%. Thus, the performance of junior high school physical education teachers in Pekanbaru City is expected to maintain and be able to improve performance professionally consistently. Keywords: Teachers Performance, Competencies of Teachers, Pekanbaru City.